Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$f\in C^{1}[0,\infty)$, $f(0)=0$ and $$ f(x)+f'(x)-\frac{1}{x+1}\int_{0}^{x}f(t)dt=0 $$ then $f'(x)=$ ?

I'v tried in the following ways. First, let $F(x)=\int_{0}^{x}f(t)dt$, then we are left to solve a second order ODE with initial condition $F(0)=0$, and $F'(0)=0$, but the problem is it seems to me that it's not that easy to solve it.

I hope there are some other ways to handle it that a one year students can understand. (I have tried to write $g(x)=f(x)e^x$ to rewrite the equation, but it doesn't make it easier)

share|cite|improve this question
Write $F(x) = (1+x) g(x)$ and plug in. This reduces the equation to first order ODE. – Marek Jan 9 '13 at 11:13
$f(x)\equiv 0$ is a solution. – Paul Jan 9 '13 at 12:09

Multiply the both sides by (x+1). Then differentiate. You'll get

$$(x+1) f''(x)+(x+2) f'(x)=0$$

Solve this equation. The solution is

$$f(x)=C_1 \text{Ei}(-x-1)+C_2$$

Now find derivative:

$$f'(x)=\frac{C_1 e^{-x}}{x+1}$$

From your condition that $f(0)=0$, it follows that $f'(0)=0$ and as such, $C_1=0$. So $f(x)$ is a constant zero.

share|cite|improve this answer
are you sure your first equation is correct? I don't think it is. – nbubis Jan 9 '13 at 15:49
the second term should be $f'(x)$. But here f is only assumed to be in $C^1$, so I think you can't do this way – sun Jan 9 '13 at 15:56
@nbubis I fixed the typo, thanks. The result does not change, it was only a typo when I copied it here. – Anixx Jan 9 '13 at 16:29
@sun I fixed the typo, thanks. The result does not change, it was only a typo when I copied it here. – Anixx Jan 9 '13 at 16:30
@nbubis I also corrected the conclusion: actually there ARE non-trivial solutions, yet the condition does not specify a unique one. – Anixx Jan 9 '13 at 16:36

You can try expanding $f(x)$ as a series around $x=-1$: $$f(x) = \sum a_n(x+1)^n$$ So that your equation becomes: $$a_n (x+1)^n + n a_n (x+1)^{n-1} - \frac{a_n (x+1)^n}{n+1} + \frac{a_n}{(n+1) (x+1)}=0$$ $$(n+1)a_n(x+1)^{n+1} + n (n+1)a_n (x+1)^{n} - a_n (x+1)^{n+1} + a_n=0$$ Since you know that $f(x)=0$, $$(n+1)a_n + n (n+1)a_n = 0 \ \ \rightarrow \ \ \forall n:a_n = 0$$ Thus the only analytic solution is $f(x)=0$, but of course ther may exist non analytic solutions as well, though I doubt it.

Edit: As @Anixx has shown there are no non analytic solutions as well.

share|cite|improve this answer
why the downvote? – nbubis Jan 9 '13 at 18:37

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.